Investigation on the Fracture Properties of Layered Carbonaceous Slate: Experiment and Numerical Simulation - Ningning Zhao; Jili Feng (Geofluids)
In order to study the influence of bedding structure on the mechanical properties of rock mass structure, this paper takes the layered carbonaceous slate in the Muzhailing tunnel as the research object, and studies the mechanical properties of layered slate under uniaxial compression and Brazilian splitting. In the numerical simulation, the discrete element software MUSEN (bonded particle model, BPM) is used to simulate the failure behavior of layered rock mass in the process of quasi-static compression. The main research contents of this paper are as follows: (1) the relationship between the microscopic Young’s modulus and the macroscopic Young’s modulus. (2) Influence of tangential shear strength and normal tensile strength on particle model. (3) The influence of different particle distributions on the simulation results. (4) The particle model with different bedding inclinations was simulated numerically. Through the comparative analysis of simulation and experiment, the results show that the mechanical response and failure mode have good consistency, and the splitting evolution process of layered slate with different bedding inclination angles is reproduced.